CareMessage Text Usage Increases Appointment Adherence in a Student-Run Free Clinic - Chen, Evan; Hoang, Peter; Garcia, Katherine; Richwagen, Nicholas; Pasarica, Magdalena (Journal of Student-Run Clinics, 2022)
Introduction: Keeping Neighbors in Good Health Through Service Clinic is a student-run, multidisciplinary free clinic dedicated to providing healthcare to uninsured, low-income patients in Central Florida. A quality improvement project was performed to decrease the rate of patient no-shows via altering the patient appointment communication method. Methods: A needs assessment was performed from June 2017 to March 2018 (n=104 patients). The intervention was implemented over an 18-month period, from April 2018 to September 2019 (n=243 patients). The intervention changed the communication method with patients such that they received appointment reminder texts two days before their appointments and responded to confirm or cancel their appointments. Phone calls were used for rescheduling, confirming cancellations, or contacting patients who had not responded to the CareMessage text. The Mann-Whitney U test was utilized for comparison of appointment no-shows, number of phone calls made, and number of patients scheduled per clinic between pre- and post-intervention groups. Results: The needs assessment showed that the average number of no-shows was 0.80 per clinic, while the average number of no-shows post-intervention was 0.26 per clinic (p=0.040). The average number of patients scheduled per clinic pre- and post-intervention was 6.90 and 7.84 (p=0.370), respectively. The average number of patients seen per clinic pre- and post-intervention was 5.93 and 6.74 (p=0.640), respectively. The average number of phone calls made weekly was 9.13 per clinic pre-intervention and 3.23 post-intervention (p<0.001). Conclusion: CareMessage is effective in reducing appointment no-shows and the number of follow-up phone calls made for appointment reminders. This intervention is important for increasing patient continuity of care, access to care, and clinic efficiency.